Overview of Lifestyle and Anthropometry of Students of the Faculty of Medicine Airlangga University During COVID-19 Pandemic - Jihadna Prima Santika Ruslan Musanip; Hermina Novida; Gadis Meinar Sari; Reny I’tishom (Indian Journal of Forensic Medicine & Toxicology, 2022)
Background: The COVID-19 pandemic has spread worldwide, forcing governments to implement quarantines asa preventive measure against the spread of the virus. Quarantine causes changes in lifestyle and anthropometrystatus among communities.Objective: To describe the lifestyle and anthropometric status of medical students batch 2018 FM UA during thepandemic. Methods: This was a descriptive study using online questionnaires from September 2020 to February2021.Results: There were variations in students’ anthropometry. Students’ average height is 161.110 cm, the averageweight is 60.308 cm, the average body mass index is 23.193 cm, the average upper arm circumference is 27.846 cm,and the average abdominal circumference is 79.621 cm. Furthermore, 145 respondents (81.9%) stated that theyexperienced changes in their lifestyle during the pandemic. A total of 89 respondents (50.3%) continued to exerciseand the other 88 respondents (49.7%) did not. Regarding the sleep pattern, 108 respondents (61%) had quitegood sleep quality and 50 respondents (28.2%) had quite poor sleep quality. For the food consumption pattern,46 respondents (26%) ate more sweet foods. Furthermore, 156 respondents (88.1%) did sedentary activities, with77 respondents (43.5%) doing sedentary behavior for more than 6 hours a day.Conclusion: During the COVID-19 pandemic, the anthropometric status of medical students batch 2018 FMUAvaried; and tend to maintain their physical activity, have quite good sleep quality, prefer eating sweet foods, anddo a sedentary behavior for a longer duration